THE OPTIMIZATION OF ISLAMIC PHILANTHROFY TO DEVELOP OF SMEs AT DOMPET DHUAFA REPUBLIKA FOUNDATION - Putra, Trisno Wardy (Jurnal Iqtisaduna, 2019)
Islamic philanthropy is one of the pillars in economic development. Islamic philanthropy consists of zakat, infaq, shadaqah and waqf. The asset turnover from the muzakki to mustahik aims to reduce poverty. Islamic philanthropy which is managed professionally through productive programs in the development of small and medium micro enterprises is expected to be able to transform mustahik to be muzakki. Republika Dompet Dhuafa Foundation as one of the national amil zakat institutions that has an economic development program is expected to be able to develop small and medium micro businesses in Indonesia. The method used in the research is descriptive qualitative method, which describes the source of fundraising and distribution of ZISWAQ at the Dompet Dhuafa Republika Foundation.